Modeling the marketing characteristics of market capacity for electrical automation - Pererva, P. G.; Kobielieva, Tatiana Aleksandrovna; Tkachev, Maksim; Tkacheva, Nadezhda (Сумський державний університет, 2017)
The article is a continuation of scientific development, the beginning of which the authors presented in the previous room. Questions of simulation of electrical characteristics of marketing automation without separate technological purposes. As the object of study selected different types of low-voltage equipment. It is proved that the most important marketing characteristics of the products the electrical business Park is articles, which are currently in operation. Existing methodical approaches to the definition of industry Park electrical automation do not provide the required accuracy of calculations. They do not fully take into account the age structure of the main technological equipment for automation of work of which is intended for electrical automation. The technique of determining industry Park, products which do not have independent technological purposes, the use of indicators of the age structure of technological equipment. For example, different groups of low-voltage equipment of the basic steps of this methodology. Suggestions the authors suggest the partition of the whole technological equipment for the three age groups and conduct separate calculations for each of them. The final coefficients of the applicability of electrical automation at the unit of technological equipment are determined based on the specific weight of each age group in the total industry Park of technological equipment. All theoretical concepts are accompanied by detailed examples of calculations.

Стаття являє собою продовження наукових розробок, початок яких авторами представлено в попередньому номері. Розглянуто питання моделювання маркетингових характеристик електротехнічних засобів автоматизації, які не мають самостійного технологічного призначення. Існуючі методичні підходи до визначення галузевого парку електротехнічних засобів автоматизації не забезпечують необхідної точності розрахунків. Вони не повною мірою враховують вікову структуру основного технологічного обладнання, для забезпечення автоматизованої роботи якого і призначені електротехнічних засобів автоматизації. Розроблена методика визначення галузевого парку виробів, що не мають самостійного технологічного призначення, з використання показників вікової структури технологічного обладнання. Підсумкові коефіцієнти вживаності електротехнічних засобів автоматизації на одиницю технологічного устаткування визначаються з урахуванням питомої ваги кожної вікової групи в загальному галузевому парку технологічного обладнання. Всі теоретичні положення супроводжуються детальними прикладами розрахунків.
Моделювання маркетингових характеристик місткості ринку електротехнічних засобів автоматизації
Keywords: park items; life; automation; marketing; coefficients of applicability; processing equipment; парк виробів; термін служби; засоби автоматизації; маркетинг; коефіцієнти вживаності; технологічне обладнання